Simulation study of blue InGaN multiple quantum well light-emitting diodes with different hole injection layers - 仵乐娟 李述体 刘超 王海龙 卢太平 张康 肖国伟 周玉刚 尹以安 杨孝东 (Chinese physics B, 2012)
InGaN-based light-emitting diodes with p-GaN and p-A1GaN hole injection layers are numerically studied using the APSYS simulation software. The simulation results indicate that light-emitting diodes with p-A1GaN hole injection layers show superior optical and electrical performance, such as an increase in light output power, a reduction in current leakage and alleviation of efficiency droop. These improvements can be attributed to the p-A1GaN serving as hole injection layers, which can alleviate the band bending induced by the polarization field, thereby improving both the hole injection efficiency and the electron blocking efficiency.